Simulation training to teach postpartum hemorrhage surgery to residents. (June 2016) - Kerbage, Y.; Debarge, V.; Lucot, J.P.; Clouqueur, E.; Rubod, C.
Abstract: Objective: Description of the aims, the framework and the results of a postpartum hemorrhage surgery workshop for residents. Study design: This article is the first publication to describe a simulation workshop for the surgical management of maternal hemorrhage. Training was divided into both theoretical and practical workshops. Four obstetrician-gynecologists supervised residents who performed all the surgical procedures on a cadaver. This training course included the oldest residents at the Faculty of Medicine of Lille and was evaluated by participants using pre-test and post-test questionnaires. Medical knowledge was also evaluated. Results: The pre-test questionnaire showed that medical knowledge for the treatment of postpartum hemorrhage was acceptable but that real practice was lacking. Eighty-six percent of the residents responded that they were not able deal with the situation correctly and most considered it stressful. The post-test questionnaire showed that training greatly improved the participants' theoretical knowledge and technical skills as well as significantly improving self-confidence. Conclusions: Based on these positive results this workshop will be included in the resident training program and also be extended to professionals as a part of the continuing medical education program.